2021
DOI: 10.1093/cvr/cvab207
|View full text |Cite
|
Sign up to set email alerts
|

Chronically elevated branched chain amino acid levels are pro-arrhythmic

Abstract: Aim Cardiac arrhythmias comprise a major health and economic burden and are associated with significant morbidity and mortality, including cardiac failure, stroke and sudden cardiac death (SCD). Development of efficient preventive and therapeutic strategies is hampered by incomplete knowledge of disease mechanisms and pathways. Our aim is to identify novel mechanisms underlying cardiac arrhythmia and SCD using an unbiased approach. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
4
17
0
Order By: Relevance
“…These have reported significant age-related changes such as alterations in beta-oxidation mechanisms, with significantly lower levels of acylcarnitines, dysregulation of the TCA cycle, and a higher abundance of proteins involved in the process of glycolysis/gluconeogenesis such as glucose-6-phosphate and fructose-6-phosphate [ 67 , 68 ]. Nevertheless, our results report additional differences between the two groups not reported previously to be influenced by age, highlighting the increased concentrations of aspartate and the lower concentrations of BCAAs, as reports in the literature have suggested higher levels of BCAAs with increasing age, leading to activation of mTOR signaling and resulting in some of the structural and functional alterations observed in the aging myocardium [ 67 , 69 , 70 , 71 , 72 ]. On the other hand, the altered substrates in the TCA cycle in the present study have not been reported in other metabolomic profiling analyses related to aging.…”
Section: Discussionsupporting
confidence: 64%
“…These have reported significant age-related changes such as alterations in beta-oxidation mechanisms, with significantly lower levels of acylcarnitines, dysregulation of the TCA cycle, and a higher abundance of proteins involved in the process of glycolysis/gluconeogenesis such as glucose-6-phosphate and fructose-6-phosphate [ 67 , 68 ]. Nevertheless, our results report additional differences between the two groups not reported previously to be influenced by age, highlighting the increased concentrations of aspartate and the lower concentrations of BCAAs, as reports in the literature have suggested higher levels of BCAAs with increasing age, leading to activation of mTOR signaling and resulting in some of the structural and functional alterations observed in the aging myocardium [ 67 , 69 , 70 , 71 , 72 ]. On the other hand, the altered substrates in the TCA cycle in the present study have not been reported in other metabolomic profiling analyses related to aging.…”
Section: Discussionsupporting
confidence: 64%
“…This prognostic association has also been observed in adolescents (McCormack et al, 2013 ). More recently, elevated BCAAs have been associated with negative cardiovascular outcomes (Du et al, 2018 ; Le Couteur et al, 2020 ; Portero et al, 2021 ; Sun et al, 2017 ).…”
Section: Bcaas Are Associated With Insulin‐resistant Obesitymentioning
confidence: 99%
“…We recently reported that elevated branched chain amino acid (BCAA) levels have proarrhythmic effects by dysregulating cardiac repolarisation and cardiomyocyte calcium homeostasis in a mammalian target of rapamycin (mTOR) pathwayedependent manner. 1 We furthermore showed that incubation of human induced pluripotent stem cellederived cardiomyocytes with high levels of BCAAs induced action potential prolongation, intracellular calcium dysregulation, and arrhythmic events, indicating a direct effect on cardiomyocyte electrophysiology. 1 However, this does not preclude the possibility that BCAAs also exert proarrhythmic effects through other mechanisms.…”
mentioning
confidence: 81%
“…1 We furthermore showed that incubation of human induced pluripotent stem cellederived cardiomyocytes with high levels of BCAAs induced action potential prolongation, intracellular calcium dysregulation, and arrhythmic events, indicating a direct effect on cardiomyocyte electrophysiology. 1 However, this does not preclude the possibility that BCAAs also exert proarrhythmic effects through other mechanisms. As mentioned by Karadeniz et al, a potential modulatory effect of BCAAs on platelet activity may be of relevance, but this requires further investigation.…”
mentioning
confidence: 81%